2020
DOI: 10.3389/fpsyt.2020.00288
|View full text |Cite
|
Sign up to set email alerts
|

Scrutinizing Domains of Executive Function in Binge Eating Disorder: A Systematic Review and Meta-Analysis

Abstract: tests and outcome measures, in order to enable more pertinent comparisons across studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 74 publications
(160 reference statements)
2
19
0
Order By: Relevance
“…Specifically, we ask whether the literature points towards behavioral impulsivity and/or compulsivity, and thus yields mechanistic insights into lapses of control during binge eating episodes. Our review extends recent work on the same constructs in anorexia and bulimia nervosa (Howard et al, 2020) and complements other up-to-date reviews (Cury et al, 2020) by including a wider range of tasks as well as animal and functional neuroimaging studies. Importantly, we note consistencies and inconsistencies across and within translational levels.…”
Section: Introductionsupporting
confidence: 61%
“…Specifically, we ask whether the literature points towards behavioral impulsivity and/or compulsivity, and thus yields mechanistic insights into lapses of control during binge eating episodes. Our review extends recent work on the same constructs in anorexia and bulimia nervosa (Howard et al, 2020) and complements other up-to-date reviews (Cury et al, 2020) by including a wider range of tasks as well as animal and functional neuroimaging studies. Importantly, we note consistencies and inconsistencies across and within translational levels.…”
Section: Introductionsupporting
confidence: 61%
“…Test meal carbohydrate–fat intake also demonstrated a somewhat strong bridge connection with the EF facet of working memory. A recent meta‐analysis showed that working memory was more impaired in individuals with both BED and obesity versus individuals only with obesity (Cury et al, 2020). It is possible that working memory may emerge as a more relevant or central bridge connection among an EF‐disinhibited eating network of individuals with a full‐threshold diagnosis of BED.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of studies in BED on executive functioning however are mixed and the number of studies is limited (Kittel, Brauhardt, & Hilbert, 2015;Lavagnino, Arnone, Cao, Soares, & Selvaraj, 2016;Van den Eynde et al, 2011;Voon, 2015;Wu et al, 2014Wu et al, , 2016Wu, Hartmann, Skunde, Herzog, & Friederich, 2013). A recent meta-analysis (Cury et al, 2020) showed alterations in working memory of individuals with BED, relative to obese people without the disorder however the effect size was small. For the other domains (inhibitory control, decision making and cognitive flexibility), no differences in performance were found between the two groups.…”
Section: Introduction and Aimsmentioning
confidence: 99%